Rentowność polskich przedsębiorstw w powiązaniu z koniunkturą gospodarczą w latach 1995-2004- badania empiryczne - Dudycz, Tadeusz; Brycz, Bogumiła (Profitability of Polish Companies in Relation with Economic Situation between 1995 and 2004 - Empirical Research, 2007)
In the article the authors present the results of empirical research on relation between fundamental profitability ratios of Polish companies and economic situation in the period 1995-2004. The analysis of factors that influence these ratios is also presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 124-135